Investigation of the excitation of the internal states of hydrogen atom - Shalenov, E.O.; Dzhumagulova, K.N.; Ramazanov, T.S.; Dzhumagulov, M.N. (Recent Contributions to Physics, 2017)
In this paper, the processes of the excitation of electron levels of hydrogen atom in an electron impact are presented. Excitation cross sections for different values of plasma dimensionless parameters are calculated that determine the state of the system. The method of quantum mechanics was used to theoretically study the processes of excitation of electron states of atom. To find the phase shifts, the Calogero equation was solved with an effective interaction potential between electron and atom in partially ionized hydrogen plasma. This effective potential takes into account the quantum-mechanical diffraction effect at small distances, the screening effect at large distances, has a finite value at distances close to zero. The excitation cross section was determined by integrating the differential scattering cross section over the scattering angles, the minimum scattering angle corresponding to this collision with the energy transfer equal to the excitation energy. The obtained results showed good agreement with the experimental data.